Respuesta :
Answer:
The required equivalent form of given expression is
[tex]\sin 3x-\sin x=2\cos 2x\sin x[/tex]
Step-by-step explanation:
Given : Expression [tex]\sin 3x-\sin x[/tex]
To find : The expression is equivalent to ?
Solution :
Applying trigonometric formula,
[tex]\sin a - \sin b = 2\cos(\frac{a+b}{2})\sin(\frac{a-b}{2})[/tex]
where, a=3x and b=x
[tex]\sin 3x-\sin x=2\cos(\frac{3x+x}{2})\sin(\frac{3x-x}{2})[/tex]
[tex]\sin 3x-\sin x=2\cos(\frac{4x}{2})\sin(\frac{2x}{2})[/tex]
[tex]\sin 3x-\sin x=2\cos 2x\sin x[/tex]
Therefore, The required equivalent form of given expression is
[tex]\sin 3x-\sin x=2\cos 2x\sin x[/tex]
The expression equivalent to (sin 3x-sin x) is 2cos(2x)sin(x) and this can be determined by using the trigonometric properties.
Given :
Expression -- (sin 3x - sin x)
The following steps can be used in order to determine the expression equivalent to (sin 3x - sin x):
Step 1 - The trigonometric properties can be used in order to determine the expression equivalent to (sin 3x - sin x).
Step 2 - Below are the properties that help to evaluate the given expression.
[tex]\rm sin \;A - sin\;B = 2cos\left(\dfrac{A+B}{2}\right) sin\left(\dfrac{A-B}{2}\right)[/tex]
Step 3 - Use the above-mentioned property in the given expression.
[tex]\rm sin \;3x - sin \; x = 2 cos\left(\dfrac{3x+x}{2}\right) sin\left(\dfrac{3x-x}{2}\right)[/tex]
[tex]\rm sin \;3x - sin \; x = 2 cos\left(\dfrac{4x}{2}\right) sin\left(\dfrac{2x}{2}\right)[/tex]
[tex]\rm sin \;3x - sin \; x = 2 cos\left(2x\right) sin\left(x\right)[/tex]
So, the expression equivalent to (sin 3x-sin x) is 2cos(2x)sin(x).
For more information, refer to the link given below:
https://brainly.com/question/24236629